2023
DOI: 10.3389/fmolb.2023.1171143
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a cryptic pocket in the AI-predicted structure of PPM1D phosphatase explains the binding site and potency of its allosteric inhibitors

Abstract: Virtual screening is a widely used tool for drug discovery, but its predictive power can vary dramatically depending on how much structural data is available. In the best case, crystal structures of a ligand-bound protein can help find more potent ligands. However, virtual screens tend to be less predictive when only ligand-free crystal structures are available, and even less predictive if a homology model or other predicted structure must be used. Here, we explore the possibility that this situation can be im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…We employed conformational ensembles of the S-BA.1 and S-BA.2 trimers in combination with template-free and highly efficient P2Rank and PASSerRank approaches to describe the available spectrum of potential binding sites and compute the residue-based pocket propensities in the ensembles of the S proteins. We combined these robust tools for the enumeration of potential pockets with a network-based weighing of the pocket probabilities to enable pocket ranking based on allosteric function which provides an adaptation and extension of the reversed allosteric communication strategy [81][82][83][84][85][86]. The central result of this analysis is the discovery of variant-specific differences in the distribution of binding sites in the BA.1 and BA.2 trimers, suggesting that small variations could lead to different preferences in the allocation of druggable sites (Figures 6 and 7).…”
Section: Allostery-guided Network Screening Of Cryptic Binding Pocket...mentioning
confidence: 99%
See 1 more Smart Citation
“…We employed conformational ensembles of the S-BA.1 and S-BA.2 trimers in combination with template-free and highly efficient P2Rank and PASSerRank approaches to describe the available spectrum of potential binding sites and compute the residue-based pocket propensities in the ensembles of the S proteins. We combined these robust tools for the enumeration of potential pockets with a network-based weighing of the pocket probabilities to enable pocket ranking based on allosteric function which provides an adaptation and extension of the reversed allosteric communication strategy [81][82][83][84][85][86]. The central result of this analysis is the discovery of variant-specific differences in the distribution of binding sites in the BA.1 and BA.2 trimers, suggesting that small variations could lead to different preferences in the allocation of druggable sites (Figures 6 and 7).…”
Section: Allostery-guided Network Screening Of Cryptic Binding Pocket...mentioning
confidence: 99%
“…By combining MD simulations, Markov state models (MSMs), and a novel MSM-based approach to aggregating docking results across structural ensembles, a recent study identified cryptic pockets targeted by allosteric myosin-II; this functional pocket is always closed in ligand-free experimental structures [84]. The cryptic binding sites were uncovered in AlphaFold-predicted ensembles of PPM1D phosphatase, and a neural network trained to evaluate the quality of docked poses predicted that this site is the most likely binding mode for the allosteric inhibitors of PPM1D [85].…”
Section: Introductionmentioning
confidence: 99%
“…Protein structure prediction is the computational task of determining the three-dimensional structure of a protein from its amino acid sequence. This process is crucial for understanding protein function, interactions, and designing novel therapeutics [1][2][3][4][5][6][7][8]. By definition, accurate prediction of protein structure from its amino acid sequence is a formidable challenge in computational structural biology, with profound implications for understanding biological function and designing novel therapeutics [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many proteins must be written off as undruggable because their structures lack pockets where an inhibitor has the potential to bind tightly enough to serve as a valuable drug (Borrel et al, 2015 ; Cox et al, 2014 ; Hopkins & Groom, 2002 ). Finally, current computational drug design methods struggle to quantitatively predict protein–ligand binding affinities, suggesting there is a fatal flaw in the single structure assumption (Jones et al, 2021 ; Meller, de Oliveira, et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%